Tachypnea without dyspnea in child with giant anterior mediastinal lipoblastoma - Dey, Sanjukta; Sarkar, Subhankar; Kundu, Soumalya (Indian Journal of Case Reports, 2022)
Lipoblastoma is a rare, benign, rapidly growing tumor. These lesions are usually asymptomatic or symptomatic due to the compression of surrounding structures. The majority of them were diagnosed in early childhood. We report the case of a 2 years old boy with giant anterior mediastinal lipoblastoma who was apparently asymptomatic except for persistent fast berating. The mass was diagnosed by computed tomography-guided needle biopsy and confirmed after removal by thoracotomy.